2020
DOI: 10.1177/1550059420965441
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Impact of Sleep Apnea/Hypopnea on the Interaction Between Various Cortical Areas

Abstract: Introduction Sleep apnea/hypopnea syndrome (SAHS) can change brain structure and function. These alterations are related to respiratory event-induced abnormal sleep, however, how brain activity changes during these events is less well understood. Methods To study information content and interaction among various cortical regions, we analyzed the variations of permutation entropy (PeEn) and symbolic transfer entropy (STE) of electroencephalography (EEG) activity during respiratory events. In this study, 57 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…This study focused on the sleep cortical FC difference without the short-term influence of respiratory events, and the EEG changed throughout the respiratory events can refer to our previous studies (Zhou et al 2020a, Zhou et al 2020b. The epochs during and after respiratory events, including event-related cortical arousal, were excluded in this study.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…This study focused on the sleep cortical FC difference without the short-term influence of respiratory events, and the EEG changed throughout the respiratory events can refer to our previous studies (Zhou et al 2020a, Zhou et al 2020b. The epochs during and after respiratory events, including event-related cortical arousal, were excluded in this study.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Previous studies suggested that the arousal stimulus in NREM is related to the level of inspiratory effort. Therefore, mechanisms of arousal in sleep apnea might also play a role in the relationship between SWS and oxygen saturation [40,41].…”
Section: Discussionmentioning
confidence: 99%